Rewriting Indonesian history : the future in Indonesia's past - Kwa, Chong Guan (2009)
"Indonesians have in the midst of all their political crises since 1945 explicitly looked back into their past for rationalizations of their present and more critically, redefine a "golden era" from which they can chart anew paths into their future. This paper examines the different challenges to the New Order version of Indonesian history and rewriting of that history for Indonesia's future. Specifically, the paper looks at the rewriting of Indonesian history (1) for the restructuring of the state and its Constitution for a more egalitarian and democratic future, (3) that reviews the swing of the pendulum in Jakarta's control of the provinces and justifies the devolution of power and decentralization of administration to the provinces, (2) which reviews the contribution of the Indonesian Armed Forces to the making of Indonesia's past and justification of its future role, (3) that acknowledges a greater role for Islam in Indonesia's past and its future."